2019
DOI: 10.1001/jamanetworkopen.2019.1474
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoking and Mortality in Asia

Abstract: Importance Understanding birth cohort–specific tobacco smoking patterns and their association with total and cause-specific mortality is important for projecting future deaths due to tobacco smoking across Asian populations. Objectives To assess secular trends of tobacco smoking by countries or regions and birth cohorts and evaluate the consequent mortality in Asian populations. Design, Setting, and Participants This pooled meta-analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 32 publications
(90 reference statements)
6
97
0
2
Order By: Relevance
“…Similar limitations were observed in cohorts from Korea. Although the authors stated that their results were comparable with findings from nationwide surveys in China and Japan, 6 these findings need to be interpreted cautiously. In addition, the study only included mainland China, Japan, Korea, Singapore, Taiwan, and India, omitting many other Asian countries.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Similar limitations were observed in cohorts from Korea. Although the authors stated that their results were comparable with findings from nationwide surveys in China and Japan, 6 these findings need to be interpreted cautiously. In addition, the study only included mainland China, Japan, Korea, Singapore, Taiwan, and India, omitting many other Asian countries.…”
mentioning
confidence: 70%
“…Yang et al 6 assessed secular trends of tobacco smoking in Asia and their association with risks of death of all causes and of lung cancer specifically by countries or regions and by cohorts. They reported that (1) smoking prevalence among Asian men continued to increase, especially in China and India; (2) the mean age for starting smoking continued to decrease, and the mean number of cigarettes smoked per day continued to increase; and (3) smoking-attributable mortalities of all causes and of lung cancer were higher in more recent birth cohorts than in older ones.…”
mentioning
confidence: 99%
“…Al comparar la prevalencia del tabaquismo en los hombres viudos según las variables demográficas, se observó una menor prevalencia en los hombres más viejos (≥80 años). Este resultado también puede estar relacionado con el sesgo de supervivencia, ya que existe evidencia clara en la bibliografía que indica la relación entre el tabaquismo y la mortalidad (54,55,56,57,58) . Para Zaitune et al (54) , la menor prevalencia observada en los adultos mayores puede explicarse por la aparición temprana de enfermedades asociadas con el tabaquismo que conducen a la recomendación de dejar de fumar, una mayor probabilidad de muerte prematura y la creciente preocupación por su propia salud, lo que hace que las personas mayores adopten comportamientos más saludables.…”
Section: Discussionunclassified
“…(S1 File). Data were extracted from the original studies [21][22] [23], which were identified via a recent systematic reviews [8] [27].…”
Section: Data Sourcesmentioning
confidence: 99%